The effect of social media marketing (SMM) on brand loyalty with brand trust and brand equity as mediation - Dani Admi; Perengki Susanto (Universitas Negeri Padang, 2023)
The purpose of this research to analyze the effect of social media marketing on Brand Loyalty by mediating Brand Equity and Brand Trust. The population in this study were all consumers of brand products and those who followed Rendang Asese's Instagram. The number of samples in this study were 224 respondents. Online surveys were used to collect the study's data, and SmartPLS software's structural equation modeling (SEM) was used to process the data. Thehresults ofrthis study indicate that (1) Social MediakMarketing has a positive and significantjeffect onmBrand Loyalty for the Rendang Asese brand on Instagram. (2) Social media marketing has ajsignificant and positive impact on brand trust on the Rendang Asese brand on Instagram. (3) Brand Equity has a significant and positive impact on brand loyalty for the Rendang Asese branddon Instagram. (4) Brand Trust has a positive effect on Brand Loyalty for the Rendang Asese brand on Instagram. (5) Social MediakMarketing has ajpositive and significant effect on Brand Equity for the Rendang Asese brand on Instagram. (6) Brand Trust has a positive effect on the Brand Equity of the Rendang Asese brand on Instagram. (7) Social MediakMarketing has ajpositive effect on Brand Loyalty which is mediated by Brand Trust on the Rendang Asese brand on Instagram. (8) Social MediakMarketing has ajpositive effect on Brand Loyalty which is mediated by Brand Equity on the Rendang Asese brand on Instagram.